Disparities in the management of cardiovascular risk factors in patients with psychiatric disorders: a systematic review and meta-analysis. Issue 16 (1st March 2018) - Ayerbe, Luis; Forgnone, Ivo; Foguet-Boreu, Quintí; González, Esteban; Addo, Juliet; Ayis, Salma
Abstract: Background: The high cardiovascular (CV) morbidity and mortality reported for patients with psychiatric disorders may possibly be due to a poorer management of CV risk factors (CVRFs). However, these healthcare disparities remain poorly understood. In this paper, studies comparing the management of smoking, diabetes, hypertension and dyslipidaemia, in patients with and without depression, anxiety, schizophrenia, bipolar or personality disorder, were reviewed. Methods: Prospective studies comparing rates of screening, diagnosis, treatment and control of CVRFs were searched in PubMed, Embase, PsychInfo, Scopus and Web of Science (inception to January 2017). The Meta-analysis of Observational Studies in Epidemiology (MOOSE) criteria were used. Studies were assessed for quality. Wherever possible, meta-analyses were conducted to summarize the findings. Results: Twenty studies, out of the 18 333 references initially identified, were included. Most studies were heterogeneous in design. Two areas permitted meta-analyses: the pooled odds ratio for quitting smoking for those with depression was 0.64 (0.49–0.80) p < 0.001; the pooled difference of glycated haemoglobin for patients with type 2 diabetes and depression was 0.18 (0.06–0.31) p = 0.005. Individual studies showed associations between: schizophrenia and lower probability of having smoking habit recorded; schizoid personality disorder and higher probability of remaining non-smokers after quitting; anxiety and poorer control of type I diabetes; depression, anxiety or schizophrenia and lower probability of having a diagnosis of hypertension; schizophrenia or bipolar disorder and lower use of antihypertensive and lipid-lowering drugs. Conclusions: A proactive clinical management, together with further studies, are needed to reduce the CV morbidity and mortality of patients with psychiatric disorders.